PELATIHAN PENYUSUNAN KEGIATAN PEMBELAJARAN PAIKEM INOVATIF BERBASIS 101 METODE GUNA MENINGKATKAN KOMPETENSI PEDAGOGIK GURU MGMP MADRASAH TSANAWIAH SE-KABUPATEN MADIUN - Ricahyono, Sigit; Arifin, Samsul (Jurnal Terapan Abdimas, 2016)
A professional teacher must be capable of mastering four basic competences namely pedagogical competence, professional competence, sosial competence, and personal competence. The result of observing and interviewing teachers who involve to the Association of Madrasah Tsanawiah Teachers (MGMP) Madiun showed that many of them still need reinforcement and enrinchment on mastering teaching methods of English. Thus, the programme aimed at increasing the pedagogical competence of teachers involving into the MGMP through having worhshop and training to design the teaching procedures implementing 101-based active, creative, efective, joyful, and innovative learning method (PAIKEM-INOVATIF). The programme was held for 5 months started on February 2014 and finished on June 2014. The result of workshop and training showed that process of understanding and practicing the metods run well. Some problems arouse during the programme were (1) the teachers still found difficulties on doing variation of teaching, (2) the teachers still feel clumsy on do peer-teaching using themethods, (3) the teachers still found difficulties on implementing some of the trained methods since the sudents have different learning characterictics. Therefore, it is suggested that the activity should be strengthen by having a programme of Lesson Study.Keywords : PAIKEM-Innovatif Teaching Methods, Workshop and Training.